(untitled) - Poliak, Milos (Doprava a spoje, 2012)
This paper deals with allocation of transport volumes. The beginning of this paper is focused on exploring of strategic documents where future goals, strategies and visions are mentioned. Fossil fuel dependency and environmental issues are examined as well. The result of this thesis is assesment of costs for virtual transport with given route. Finally comparison of results of rail and road transport costs is committed. Result of this comparison and possible solutions are discussed in order to make railway transport be more attractive for potential customers.